Analisis Pemulihan Usaha Mikro, Kecil, dan Menengah (UMKM) Berbasis Komunitas - Ju im; Sri Indarti; Titi Darmi (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2021)
The recovery policy for Micro Small, and Medium Enterprises (MSMEs) during the COVID-19 pandemic has been implemented by the Central Bengkulu Regency Government. This study examines the implementation of MSME recovery policies in Central Bengkulu using the Community theory of David C. Korten. The analysis is targeted to provide recommendations in terms of the interests of the MSME community and the orientation of the public interest. The results showed that the MSME recovery program was through the assistance of Banpres/productive business capital and the Regional Incentive Fund in Central Bengkulu Regency. In general, the implementation of the recovery of MSMEs in the Bengkulu Tengah Regency has been running according to the procedure. The policies implemented have played a role in helping and supporting the recovery of MSMEs to survive and thrive. Several obstacles, dynamics arise in the implementation and sustainability of policies on a community basis. Effective policy development needs to be accompanied by intensive cluster-based follow-up assistance. It is necessary to systematically update digital-based MSME data for coaching with programmatic and continuous consolidation.